Water Resources of Israel: Trackrecord of the Development - Nicolai S. Orlovsky; Igor S. Zonn (Проблемы постсоветского пространства, 2018)
Israel is a country in the Near East consisting for 95% of the arid regions in which 60% of the territory are covered by the Negev Desert. Therefore, the water resources are scant here and formed mostly by atmospheric precipitations. In the period from 1989 to 2005 the average precipitations were 6 billion cu. m, of which 60–70% were evaporated soon after rainfalls, at least 5% run down by rivers into the sea (mostly in winter) and the remaining 25% of precipitations infiltrated into soil from where the greater part of water got into the sea with ground waters. In Israel there are two groups of water resources: surface and underground. Israel is not rich in surface waters. The natural reservoir of surface fresh water is the Kinneret Lake in the northeast of the country. It gets water from the Jordan River and its tributaries. The average annual amount of available water of this lake is around 370 million cu. m, which accounts for one-third of the country’s water needs and still higher share of the drinking water needs. The greater part of fresh waters (37% of water supply of Israel as of 2011) in this country is supplied from ground water sources. Owing to insufficiency of available natural resources, unevenness of precipitations by years and seasons and with the growth of the population and economic development the issues of provision with the quality drinking water of the population as well as agriculture and industry, rehabilitation of natural environment cause permanently growing concern. In view of the water shortage untiring efforts have been taken to improve the irrigation efficiency and to reduce water use by improving the efficacy of irrigation techniques and application of advanced system management approaches. Among the water saving technologies applied in Israel there are: drop irrigation, advanced filtration, up to date methods of water leak detection from networks, rainwater collection and processing systems. At the same time such measures as water flow measurements, policy of water price formation, changeover to cultivation of valuable crops, thermal water recycling, computer-based and remotely controlled irrigation are also applied. The search for new techniques of fresh water production is going on. Water saving is considered the most reliable and less costly method to increase water resources of the country, And this task is being accomplished in all sectors. In 1964 the National Water Carrier of Israel was constructed. The main task of this project is to achieve the reliable compensation of the difference between water income in various regions (north and south), in different seasons (summer and winter) and in different years (with sufficient and insufficient precipitations). In 1999 the Israel government initiated the long-term large-scale program of sea water desalination for production of drinking water for internal use. Reverse osmosis was adopted the basic technique for desalination of brackish and sea water. Currently there are five sea water desalination plants producing about 600 million cu. m of desalinated water per year which is equivalent to approximately 42% of the country’s drinking water needs. Israel adopted the General Plan of Water Economy Development for 2010–2050, which envisages complete coverage of water deficit by way of entire wastewater treatment and construction of additional sea water desalination facilities with a capacity to 1500 million cu. m by 2050. Any additional desalinated water that may become available in these years will be used for replenishing the water supply in Israel.